Influence of surface modifying macromolecules (SMMs) on polyethersulfone hollow fiber membranes for water separations - Bolong, N.; Ismail, A. F.; Salim, M. R.; Rana, D.; Matsuura, T. (2007)

(untitled)
The objective of this work is to modify the polyethersulfone (PES) hollow fiber membranes by blending with Surface Modifying Macromolecules (SMMs) which were able to introduce charges at the membrane surface. To study the effects of SMMs, PES solutions with and without blending SMMs were spun by the dry–wet phase inversion method. The membranes were characterized by ionic solutes permeation and Field Emission Scanning Electron Microscopy (FESEM). There was no significant difference in the membrane morphology between the membranes with and without SMM blending, indicating that the morphology of the base polymer remained relatively unchanged. However, based on Energy Dispersive X–ray (EDX) analysis, the presence of SMM’s elements at the surface of the SMM blended membranes was detected. The pure water permeation rates were found two times increased with the existence of SMMs, while rejection towards ionic solutes remained relatively unchanged